Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species - Doughty, Paul; Bourke, Gayleen; Tedeschi, Leonardo G.; Pratt, Renae C.; Oliver, Paul M.; Palmer, Russell A.; Moritz, Craig (Zootaxa, 2018)
Recent advances in molecular genetic techniques and increased fine scale sampling in the Australian Monsoonal Tropics (AMT) have provided new impetus to reassess species boundaries in the Gehyra nana species complex, a clade of small-bodied, saxicolous geckos which are widely distributed across northern Australia. A recent phylogenomic analysis revealed eight deeply divergent lineages that occur as a series of overlapping distributions across the AMT and which, as a whole, are paraphyletic with four previously described species. Several of these lineages currently included in G. nana are phenotypically distinct, while others are highly conservative morphologically. Here we use an integrated approach to explore species delimitation in this complex. We redefine G. nana as a widespread taxon with complex genetic structure across the Kimberley of Western Australia and Top End of the Northern Territory, including a lineage with mtDNA introgressed from the larger-bodied G. multiporosa. We describe four new species with more restricted distributions within the G. nana complex. The new species are phylogenetically divergent and morphologically diagnosable, and include the relatively cryptic G. paranana sp. nov. from the western Northern Territory, the large-bodied G. pseudopunctata sp. nov. from the southern Kimberley ranges, G. granulum sp. nov., a small-bodied form with granules on the proximal lamellae from the north-west and southern Kimberley ranges and the small-bodied G. pluraporosa sp. nov. restricted to the northern Kimberley. Our revision largely stabilises the taxonomy of the G. nana complex, although further analyses of species limits among the remaining mostly parapatric lineages of G. nana sensu stricto are warranted.